‘Radish’ in the rectum - Maharjan, Shanta Bir; Manandhar, K; Joshi, A; Lamichhane, D; Shah, JN (Journal of General Practice and Emergency Medicine of Nepal, 2011)
A 38 years male was referred to our hospital for sigmoidoscopy and removal of foreign body from rectum. Patient gave history of insertion of ‘radish’ through his anus. He developed pain, distension, vomiting and obstipation next day. On presentation abdomen was board like rigid and distended. He underwent emergency laparotomy and removal of radish from pelvis. He had eventful post operative days. He didn’t disclose why he inserted radish into his rectum!